The Dysfunction Of Tigo Tungku Sajarangan Local Institutions In Handling Cases Of Early Marriage - Yunanda, Dhea; Eriyanti, Fitri (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2024)
This research is motivated by the large number of data found on early marriage actors in Nagari Pasie Laweh which is caused by the dysfunction of Tigo Tungku Sajarangan which runs less than optimally. This study aims to analyze the dysfunction of the local institution of Tigo Tungku Sajarangan which is less than optimal in dealing with cases of early marriage and the revitalization of the local institution of Tigo Tungku Sajarangan dealing cases early marriage. This research uses structuration theory by Anthony Giddens and social change theory by Wilbert Moore. The approach used is qualitative with the type of case study research. Research informants were determined by purposive sampling technique with the following criteria: Density of Nagari as Ninik Mamak, Syarak Nagari Customary Council as Alim Ulama, Smart Clever, early marriage actors, parents, and society. Data was collected using observation, interviews, and documentation studies. The data validity test includes credibility, transferability, dependability, and confirmability tests. Analysis of the data using the interactive analysis model of Miles and Huberman. The results showed that the dysfunction of the local institution Tigo Tungku Sajarangan in handling cases of early marriage did not run optimally due to the absence of strict sanctions, giving consent to marriage, lack of social control, propaganda rewards, lack of cooperation, lack of deliberation, and not optimal inculcation of values ​​and norms. . There is a revitalization of the function of the Tigo Tungku Sajarangan local institution that is running less than optimally, namely by being a role model, giving attention, appeals, reorientation, maintaining social unity, and motivating the younger generation.